RATIONALIZATION OF BANK CAPITAL CONCENTRATION - Petr Viktorovich Akinin; Valentina Petrovna Akinina (Вестник Северо-Кавказского федерального университета, 2022)
The article offers an analysis of the processes related to consolidation of the bank sector in Russia, their bivariant forecast, as well as some recommendations regarding rationalization of bank capital.